Maternal and child health in Israel: building lives. Issue 10088 (24th June 2017) - Rubin, Lisa; Belmaker, Ilana; Somekh, Eli; Urkin, Jacob; Rudolf, Mary; Honovich, Mira; Bilenko, Natalya; Grossman, Zachi
Summary: Israel is home to a child-oriented society that values strong family ties, universal child benefits, and free education for all children from 3 years of age to school grade 12. Alongside the universal health-care services that are guaranteed by the National Health Insurance Law and strong, community-based primary and preventive care services, these values have resulted in good maternal and child health. In 2015, infant and maternal mortality (3·1 deaths per 1000 livebirths and 2·0 deaths per 100 000 livebirths, respectively) were lower than the mean infant and maternal mortality of countries within the Organisation for Economic Co-operation and Development. Israel has already exceeded the developed regions' Sustainable Development Goal 2030 targets for maternal mortality, neonatal mortality, and mortality in children younger than 5 years in all population groups. Yet these accomplishments are marred by Israel's high prevalence of child poverty (more than 30%), particularly among Arabs (63%) and ultra-Orthodox Jews (67%). Although infant mortality has improved in all subpopulations since Israel was founded in 1948, infant mortality among Arabs is still more than twice as high as among Jews. To address these disparities in health, the Israeli Ministry of Health has created a special division and has funded an intervention programme to reduce the infant mortality among Bedouin Arabs. Other interventions include targeted and culturally appropriate health-care programmes and services for communities with a high number of at-risk children and young adults, dental health service for all children up to 15 years, and improved collaboration between health, education, and welfare services. The challenges faced by the Israeli health-care system include a growing trend towards medicalisation of prenatal care, ensuring staff are trained to treat developmental, behavioural, and psychosocial issues in children and their families, securing sustainable funding for health promotion and injury prevention programmes, expanding and improving the coordination of services for children with special needs or who are at risk, and programme assessment. Ensuring adequate funding for dedicated, preventive paediatric care and taking action on a nationwide scale to reduce child poverty are essential for maintaining health gains in children. In this Series paper, we describe the health indices, highlight disparities, and discuss the challenges in delivering and maintaining maternal and child health care in Israel.